Синтаксические фразеологизмы русского языка и их перевод на норвежский язык (Syntactic Phraseological Structures in Russian and their Norwegian Translations) - Olga Komarova; S. B. Stepanova (Poljarnyj Vestnik: Norwegian Journal of Slavic Studies, 2000)
The notion of syntactic phraseological structures in Russian was introduced in the Russian Grammar of 1980. Here it is argued that certain syntactic struc- tures (about 30) can be considered phraseological due to their compact and stable usage and to the fact that their specific semantic structure cannot be understood as a direct sum of the meanings of their components (e.g., den' kak den', emu ne do smecha, vse ljudi kak ljudi). The semantics of these structures, however, has not been the subject of special studies. There exists only one book by A. B. Velichko, where an attempt at semantic classification has been made with a focus on the needs of a foreign student. As it turns out,this classification is not detailed enough. The authors of this article suggest certain changes in Velichko's classification considering specific emotional colouring of some of these structures. The authors provide illustrative exam- ples, the translations of which into Norwegian show that different devices render the emotional meanings of these structures. It can be concluded that in certain cases it is possible to use similar syntactic structures as in Russian, but in most cases it is necessary to find other expressive means (either lexical or syntactic).